Management of nasal fractures in sports - Patel, Y.; Goljan, P.; Pierce, T. P.; Scillia, A.; Issa, K.; McInerney, V. K.; Festa, A. (Sports Medicine, 2017)
Nasal fractures represent approximately 60% of all maxillofacial injuries that occur in athletic activities; however, there are no current guidelines regarding immediate sideline management of these injuries. Therefore, the purpose of this article was to (1) summarize the anatomy, etiology, and incidence of nasal fractures, and (2) evaluate the current body of literature regarding immediate on-field and subsequent outpatient management. It is imperative to establish that the athlete`s airway is not compromised and there are no other severe concomitant injuries, such as a concussion, ocular injury, or leakage of cerebrospinal fluid. Immediate closed reduction should not be attempted unless there is airway compromise or the practitioner has experience in performing it. The majority of athletes with these injuries in isolation may return to play; however, in our practice, we recommend they wear a face mask for 6 weeks after their injury. Despite our recommendations, we know there is a paucity of clinical studies on immediate sideline and longer-term management. Future studies should focus on establishing therapeutic algorithms that will allow physicians to make treatment recommendations to patients with strong evidence to support their decision.